Evaluation of Precision Feeding Standardized Ileal Digestible Lysine to Meet the Lactating Sow’s Requirement and Maximize Piglet Growth Performance - Mikayla S. Spinler; Jordan T. Gebhardt; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Hyatt L. Frobose; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 56 mixed parity sows (DNA 241, Columbus, NE) and litters (DNA 241 × 600) were used across two batch farrowing groups to evaluate the effects of precision feeding SID Lys during lactation. Sows were blocked by parity and allotted to 1 of 3 treatments on day 2 of lactation (the day after the start of farrowing). The first treatment was a control treatment where sows were provided a 1.10% SID Lys diet throughout lactation. The second and third treatments included sows fed either a static blend curve or a dynamic blend curve. Both blend curve treatments utilized the Gestal Quattro Opti Feeder (Jyga Technologies, St-Lambert-de-Lauzon, Quebec, Canada) to blend a low and high Lys diet to target a specific SID g/d of Lys intake for each day of lactation. The only difference between the static blend curve and dynamic blend curve was that the dynamic blend curve of the low and high Lys diet was adjusted every 2 days based on a rolling average of Lys intake to more closely reach target g/d of Lys intake while the static blend curve was not adjusted throughout lactation. Lysine intake curves were based on the NRC (2012) model estimates, but targets were increased by 20% to reach an average Lys intake of approximately 60 g/d across parities. Dietary treatments for sows on the blend curve treatments were formed by blending a low Lys diet (0.40% SID Lys) and the control high Lys diet (1.10% SID Lys). Actual SID Lys intake was 97% of the targeted g/d for sows fed the static blend curve and 96% of targeted g/d for sows fed the dynamic blend curve. Sows fed the control treatment had greater Lys intake (g/day;P<0.05) compared to sows fed either of the blend curve treatments, with no differences between the two blend curve treatments (P>0.05). No differences in sow ADFI or sow body weight, backfat, or loin depth at entry or weaning were observed among treatments (P>0.05). There were no differences among treatments observed in litter size, piglet weight at birth or weaning, ADG, and litter weight or ADG (P>0.05). Because sows fed either blend curve had a numerically greater ADFI, no differences in sow feed cost were observed (P>0.05). Sows fed the control treatment excreted more N and had a higher serum urea N concentration compared to sows fed either blend curve treatment (P>0.05). Based on the results of the study, blending a low and high Lys diet can be used during lactation to decrease N excretion and achieve similar piglet growth performance compared to results for piglets from sows fed only a high Lys diet throughout lactation. Furthermore, these data would suggest that 60 g/d of SID Lys is sufficient to maximize litter weight gain for litter sizes of 13.5 weaned piglets.
Keywords: feed blending; lysine; precision feeding; sow; piglet